Predicting Anxiety and Depression Among Patients With COVID-19 in Concentrated Isolation at Medical Camps in Vietnam: A Descriptive Cross-Sectional Study - Trang, Vu Thi Thu; Huynh, Khoa Le Anh; Truong, Huyen Thi; Nguyen, Hue Thi; Hoang, Giang Truong; Dao, Dat Quang; Van Vu, Ut; Hassan, Zair; Nguyen, My Ngoc Ha; Truong, Le Van (Frontiers in Psychiatry, 2022)
Introduction: The study aims to assess the requirement for anxiety and depression treatment for COVID-19 patients at medical camps in Bac Giang province, Vietnam. This information can help improve government policy to reduce anxiety and depression for COVID-19 patients. Methods: A total of 427 COVID-19 patients participated in the survey from June 5 to 15, 2021, at Bac Giang province. The survey included 17 questions about the general characteristics of the patients, 15 questions to assess common COVID-19 symptoms, the Patient Health Questionnaire-9 (PHQ-9), and General Anxiety Disorder-7 (GAD-7) scores, and four questions to assess hospital reviews, including facilities, food, medical staff, and living conditions. Logistics regression analyses were utilized to assess the association between COVID-19 symptoms and high anxiety and depression (HAD) status. Results: Logistic regression analysis evaluated the risk factors in need of intervention. Our study showed lower hospital review scores (odd ratio = 0.98, 95% confident interval = 0.97 – 0.99) were found to be a risk needing intervention. It was also identified that older patients (odd ratio = 1.10, 95% confident interval = 1.03 – 1.18), females (odd ratio = 1.31, 95% confident interval = 1.09 – 1.31), patients who were the primary income earners in the family (odd ratio = 1.15, 95% confident interval = 1.03 – 1.28), patients who had headaches (odd ratio = 1.16, 95% confident interval = 1.06 – 1.21), and patients who had joint pain (odd ratio = 1.17, 95% confident interval = 1.06 – 1.30) were risk factors for HAD status. Conclusion: Our research shows that every 10-year age increase was associated with a 10% increase in the likelihood of HAD status. Study subjects being the primary income earners were also associated with a 15% increased risk of having HAD status. This study showed that a decrease in family income due to COVID-19 caused an increase in high-level anxiety/depression status.